Relationship of Physical stress and Hypertension among Cardiovascular Disease Patients - Ali, Safdar; Akhter, Hamza; Altaf, Kisa Fatima; Noushad , Shamoon; Asghar, Naila; Ahmed , Syed Saad; Ahmed , Sadaf (International Journal of Endorsing Health Science Research, 2016)
Objective: The aim of the study is to find out amount of physical stress among cardiovascular disease (CVD) patients and its relation with hypertension. Background: Physical stress is defined as a pressure – force and strain a state of physical mental tension. Stress is among the mental factors that has for some time been recorded among the potential. Furthermore, essential hazard variables of hypertension and coronary illness. Methodology: A cross-sectional study was conducted in the patients of department of Cardiology at tertiary hospitals, Karachi, from January 2014 to December 2014. Sadaf stress scale (SSS) 2.0 was used to find out the physical stress. Results: It showed physical stress among CVD patients about n=39 (43.3%) have moderate physical stress. which was decreased over time after 5 year of illness as compared to the patient who have disease for less than 5 years. While systolic blood pressure among subjects with severe physical stress showed an average systolic B.P. of 147mmhg, moderate have 146mmhg and patients with mild physical stress have 135mmhg. Conclusion: This report concluded moderate physical stress among CVD patients which was decrease over time due different coping mechanism and blood pressures are directly related to severity of physical stress mainly systolic which lead to hypertension.